Shaping musical performance culture in a minority language context: The Gwynn Publishing Company's Welsh and English song-translations. Issue 3 (2nd September 2022) - Ifan, Elen
ABSTRACT: This article examines the catalogue of a prominent twentieth-century Welsh musical publishing company, the Gwynn Publishing Company, in its first decade. The act of performance as it connects to the development and evolution of culture informs the discussion, and the company's director William Sidney Gwynn Williams, along with writer and translator Thomas Gwynn Jones, are considered as agents of both translation and the musical performance culture. The article discusses texts published by the company as well as individual translation strategies used, shedding light on the motives and objectives of these cultural agents. This, in turn, enables an exploration of how a flexible translation approach can be used by agents of minority language cultures to contribute to an ongoing process of performance of national identity and culture.